2004
DOI: 10.1038/sj.npp.1300433
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Fluoxetine in Animal Models of Anxiety and Depression

Abstract: The onset of the therapeutic response to antidepressant treatment exhibits a characteristic delay. Animal models sensitive to chronic, but not acute, antidepressant treatment are greatly needed for studying antidepressant mechanisms. We initially assessed four inbred mouse strains for their behavioral response to chronic treatment with the selective-serotonin reuptake inhibitor fluoxetine (0, 5, 10 mg/kg/day in drinking water), which is used for the treatment of mood and anxiety disorders. Only the highly anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
490
7
10

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 609 publications
(553 citation statements)
references
References 45 publications
46
490
7
10
Order By: Relevance
“…In the present work, we show that when LH animals are chronically treated with FLX for 21 days, as expected from other reports (Dulawa et al, 2004), reversion of depressivelike behavior is observed. We demonstrate that a behaviorally successful treatment with the antidepressant FLX fully reverses the diminution of synaptic proteins induced in the CA3 by exposure to the LH paradigm, an animal model of depression.…”
Section: Discussionsupporting
confidence: 93%
“…In the present work, we show that when LH animals are chronically treated with FLX for 21 days, as expected from other reports (Dulawa et al, 2004), reversion of depressivelike behavior is observed. We demonstrate that a behaviorally successful treatment with the antidepressant FLX fully reverses the diminution of synaptic proteins induced in the CA3 by exposure to the LH paradigm, an animal model of depression.…”
Section: Discussionsupporting
confidence: 93%
“…However, these results are in agreement with data from other labs that have delivered fluoxetine orally. Dulawa et al (2004) found that 4-day fluoxetine treatment had no effect on either the open field test, a measure of general activity and anxietylike behavior, or the forced swim test (FST), another measure of behavioral despair. Similarly, Caldarone et al (2003) found that 21 days of treatment with the tricyclic antidepressant amitriptylene reduced FST immobility to a greater extent than 4 days of treatment.…”
Section: Dose Responsementioning
confidence: 99%
“…This burying behavior is quantifiable and sensitive to anxiolytics 45,46 . Hyponeophagia (novelty suppressed feeding) has also been used to assess anxiety-like behavior in rodents; in a novel environment, hungry mice exhibit an increased latency to feed that is sensitive to BZDs and SSRIs 47,48 .…”
Section: Measuring Anxiety-related Behaviors In Rodentsmentioning
confidence: 99%